Systematic dissemination of a preschool physical activity intervention to the control preschools - Howie, Erin; Brewer, A.; Brown, W.; Saunders, R.; Pate, R. (2016)
For public health interventions to have a meaningful impact on public health, they must be disseminated to the wider population. Systematic planning and evaluation of dissemination efforts can aid translation from experimental trials to larger dissemination programs. The Study of Health and Activity in Preschool Environments (SHAPES) was a group-randomized intervention trial conducted in 16 preschools that successfully increased the physical activity of preschool age children. Following the completion of the research study protocol, the intervention was abbreviated, modified and implemented in four preschools that participated as control preschools in the original research study. The purposes of the current study were to describe the process of refining the intervention for dissemination to the control preschools, and to assess the acceptability of the resulting abbreviated intervention delivery. Five overarching behavioral objectives, informed by process evaluation, data from the original trial and collaboration with intervention teachers, were used to guide the implementation. Teachers in the dissemination classrooms reported high levels of acceptability, potential for sustainability of the program, and positive results in knowledge, skills, and child outcomes. Researchers can include a systematic approach to dissemination of effective intervention elements to the control participants in experimental studies to inform future dissemination efforts and begin to bridge the dissemination gap.